A case report Management of Foreign Body “Scarf Pin” Stuck in the Left Bronchus Through Rigid Bronchoscope: Article Case Report - Septiany, Dwi Tika; Asyari, Ade (Jurnal Ilmu Kesehatan Indonesia, 2025)
Introduction: Aspiration of foreign body a scarf pin happens in teenagers who wear the headscarf. The diagnosis of foreign body aspiration is established on the anamnesis, choking history and chest X-ray. Rigid bronchoscopy is an option to extracted foreign body in the tracheobronchial tree. Objective: Understanding diagnosis dan management of foreign body scarf pin stuck in the left bronchus. Case Report: Reported a case 14-year-old girl came to Emergency room with chief complaint of accidentally choked a pin 7 hours before admission. Chest X-ray examination revealed a homogeneous opacity of metallic density in the projection of the left primarius bronchus at the level of the thoracic vetebra 6-7. The patient was diagnosed foreign body a pin at the left bronchus. Patient was treated by diagnostic and therapeutic rigid bronchoscope. Conclusion: A headscarf pin foreign body can be found in the left bronchus because the tracheal angle symmetric and effect of Bernoulli phenomenon. Rigid bronchoscope can be used to diagnostic and therapeutic in this case. If there are postoperative complications such as laceration and perforation of the bronchus, immediately consult to the Department of Cardiothoracic Vascular Surgery for further management Kata kunci: Foreign body in bronchus; rigid bronchoscopy; headscarf pin